The Importance of Indicators : Product Quality Direct Selling and Advertising in Solving The Problem of The Pizza Hut Purchase During The Covid-19 Pandemic - Yoga Adiyanto (Ilomata International Journal of Management, 2022)
Pizza Hut made various efforts to boost sales in the face of business challenges in the midst of the pandemic. One of the ways to do this is by picking up the ball by selling it on a number of roads ( Gowest.id ). In addition, the strategies used by Pizza Hut are prioritizing delivery order and take away services at Pizza Hut outlets , marketing products on the roadside , holding discount promos; and n create new variants in the Pizza menu and improve the quality of its products . This study aims to determine the effect of product quality, direct selling and advertising on purchasing decisions on Pizza Hut consumers. This research is a quantitative research, taking the place of research at Pizza Hut Serang . The data used in this study are primary and secondary data obtained from distributing questionnaires to Pizza Hut consumers . The sample used is 100 respondents . Data analysis used multiple linear regression technique using SPSS program. The results of this study indicate that product quality has an effect on purchasing decisions . Direct Selling has no effect on purchasing decisions. Advertisement influence on purchasing decisions. and simultaneously variable product quality, direct selling and advertising affect purchasing decisions on Pizza Hut consumers.